Cryopreservation of oil palm (Elaeis guineensis) zygotic embryos using the vitrification technique - Uma Rani Sinniah (Malaysian Society of Plant Physiology, 2019)
Oil palm (Elaeis guineensis) is one of the main plantation crops in Malaysia. Due to its importance it is vital that a broad genetic base is conserved for future improvement. Oil palm germplasm has been mainly conserved in field genebanks due to its recalcitrant seed properties. Field conservation is costly to maintain and require much land and management to control pests and diseases. For long-term conservation, the use of in vitro techniques especially cryopreservation has been most promising. Cryopreservation is the storage of materials under ultra-low temperature of liquid nitrogen. Various methods of cryopreservation are available, but this study evaluates the potential of using vitrification technique as opposed to the desiccation technique on survival of cryopreserved oil palm embryos. The type of loading and vitrification solution used often influences the vitrification process and is species specific. Time of exposure to both loading and vitrification solution also plays as important role as prolonged exposure will result in toxicity. In this study seven loading solutions were tested and the best loading solution was tested for response to exposure time. Subsequently, the effect of five vitrification solution was tested. The best survival percentage obtained was compared with the survival obtained using the desiccation method. It appears that the vitrification technique is not appropriate for oil palm as only around 10% survival was obtained while circa 50% survival can be obtained using the desiccation technique.